Evaluation of the Effectiveness of the Cheap Market Operation Program in Controlling Inflation in East Belitung Regency: An Approach Based on William N. Dunn's Public Policy Theory - Dimas Prahmana; Helen Dian Fridayani; Muhammad Eko Atmojo (Jurnal Ilmu Pemerintahan : Kajian Ilmu Pemerintahan dan Politik Daerah, 2026)
This study aims to evaluate the extent to which the implementation of the Cheap Market Operation Program contributes to reducing the inflation rate in East Belitung Regency. Regional inflation is a serious challenge because it has a direct impact on people's purchasing power, especially vulnerable groups. This study uses a descriptive qualitative approach with a case study method and analyzes data based on public policy evaluation indicators according to William N. Dunn, namely effectiveness, efficiency, adequacy, fairness, and accuracy. The findings of the analysis show that the Cheap Market Operation Program has not been successful in controlling inflation, as it still requires refinement in policy formulation that not only focuses on price stability but also functions as a strategic tool in controlling inflation at the regional level. The contribution of these findings shows that policy formulation is very important, as is the policy of controlling commodity prices.